Biological–physical processes regulate autumn prey availability of spiny icefish Chaenodraco wilsoni in the Bransfield Strait, Antarctic. Issue 1 (15th June 2022) - Yang, Qingyuan; Reid, Keith; Zhu, Guoping
Abstract: This study examines the adaptability of a Southern Ocean predator, which is dependent on Antarctic krill ( Euphausia superba ), to potential changes in food availability. Muscle fatty acids (FAs) of the spiny icefish Chaenodraco wilsoni collected from three areas in the Bransfield Strait (BS), northern Antarctic Peninsula during February–April 2016 give a good representation of their feeding variability. The compositions of 22:6n3 (DHA) and 20:5n3 (EPA) were both higher in the Transitional Zonal Water with Bellingshausen influence (TBW)‐controlled C. wilsoni than in the Transitional Zonal Water with Weddell Sea influence (TWW)‐controlled fish. This was positively correlated with photoadaptation and carbon sequestration in TBW‐controlled phytoplankton. Results for the FAs 16:1n7, 16:0, DHA and EPA indicate the presence of dinoflagellates in all three areas, suggesting that during late summer and early fall, there is a seasonal phytoplankton succession, where small phytoplankton become dominant, in the BS. In addition, the compositions of some long‐chain FAs (>20, such as 20:0, 20:1, 22:0 and 22:1n9) and ∑18 indicated that the food chain based on flagellates and copepods was more apparent in TWW‐controlled C. wilsoni, especially the effect of El Niño‐Southern Oscillation (ENSO) on the variation of prey communities in TWW‐controlled areas. FA markers such as SFA/(PUFA+MUFA), ∑15 + ∑17 and ARA were more pronounced in TWW‐controlled C. wilsoni, indicating a more strongly carnivorous and benthic food source. In the TBW–TWW confluence, the complex hydrological structure, including the presence of a large number of mesoscale eddies, allows rich nutrients and krill larvae to remain in it, providing a rich food source for the C. wilsoni . Overall, the FA data of this study show that the diet of C. wilsoni varies in different marine environments, aiding their survivability at the face of climate change.